2015
DOI: 10.1016/j.pmn.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Procedural Pain: How Far Have We Come? An Ethnographic Account

Abstract: In this ethnographic study, the author explores the pediatric procedural pain management practice of healthcare providers in a non-pediatric emergency department. Data were collected for 5 months with over 100 hours of observation. Six key informants were interviewed, and 44 pediatric procedural interactions with 27 healthcare providers during the treatment of children two to eight years of age undergoing procedures were observed. Other information gathered included documents from the institution, and pain rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Previous studies have described the use of holding, forcing, and restraint on children in medical and clinical procedures, which relates to the use of force on children in this study. However, the focus in previous studies was not specific to challenging procedures (Bray et al, 2018;Brenner, 2013;Crellin et al, 2011;Cummings, 2015;Kangasniemi et al, 2014;Kirwan & Coyne, 2016;Lloyd et al, 2008;Lombart et al, 2019;Svendsen et al, 2017;Svendsen et al, 2018). Ensuring the children's co-determination and participation was important in this study of challenging procedures and is in line with general principles of affirming the child's cooperation and listening to the child's voice (Bray et al, 2018;Kirwan & Coyne, 2016).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have described the use of holding, forcing, and restraint on children in medical and clinical procedures, which relates to the use of force on children in this study. However, the focus in previous studies was not specific to challenging procedures (Bray et al, 2018;Brenner, 2013;Crellin et al, 2011;Cummings, 2015;Kangasniemi et al, 2014;Kirwan & Coyne, 2016;Lloyd et al, 2008;Lombart et al, 2019;Svendsen et al, 2017;Svendsen et al, 2018). Ensuring the children's co-determination and participation was important in this study of challenging procedures and is in line with general principles of affirming the child's cooperation and listening to the child's voice (Bray et al, 2018;Kirwan & Coyne, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Many previous studies have examined the use of holding, forcing, and restraint on children during medical and clinical procedures (Bray et al, 2018;Brenner, 2013;Crellin et al, 2011;Cummings, 2015;Kangasniemi, Papinaho, & Korhonen, 2014;Kirwan & Coyne, 2016;Lloyd, Urquhart, Heard, & Kroese, 2008;Lombart, De Stefano, Dupont, Nadji, & Galinski, 2019;Svendsen, Moen, Pedersen, & Bjørk, 2018;Svendsen, Pedersen, Moen, & Bjørk, 2017). Although Svendsen et al (2017) raised disparate views on the concept of restraint and its use, many studies have reported the use of restraint on children during procedures as a common and daily practice (Bray et al, 2018;Brenner, 2013;Crellin et al, 2011;Cummings, 2015;Kangasniemi et al, 2014;Lombart et al, 2019), which is also referred to as therapeutic holding (Kirwan & Coyne, 2016). Other studies have also found that parents were uncomfortable or did not accept the use of restraint on their children (Brenner, 2013;Svendsen et al, 2018) and were concerned about the long-term consequences for the children (Svendsen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] The injection regimen constitutes repeated episodes of procedural pain for Aboriginal children. Procedural pain management is known to be underutilised and poorly managed in children [34][35][36][37][38][39] as well as for Aboriginal patients. 40 Aboriginal patients may under-report pain leading to the erroneous assumption that they feel pain less or are more tolerant and stoic.…”
Section: Discussionmentioning
confidence: 99%
“…Distressing procedures such as taking blood tests, administering medication, x-ray, eye drops and nebulizer require children to be held tightly, without analgesia, in current practice (Bray et al, 2015;Brenner, 2013). Healthcare professionals consider it better to restrain the child so that the procedure is implemented (Cummings, 2015;Ives & Melrose, 2010;Söderbäck, 2013) and the pain and discomfort the child is exposed to justified by the fact that adults believe it is in the child's best interest. The pain and discomfort healthcare professionals conduct against the will of the child is often justified by adults as contributing to what is best for the child (Llyod, Urquhart, Heard, & Kroese, 2008).…”
Section: Restraint During Clinical Proceduresmentioning
confidence: 99%